An investigation on performance of Stock market companies owned by the banking system in Iran: A Development Approach - Towhid Firoozan Sarnaghi; Mohammad reza Monjazeb; Leila Khosravi (پژوهش‌های برنامه و توسعه)
Regional development and deprivation is one of the priorities of development programs and has been emphasized in various economic development plans of the IRAN. One of the prominent examples of this type of development is the establishment and formation of industrial companies and factories in different regions of the country. From this point of view, evaluating the experience of banks Ownership and shareholding can be useful and can be applied under conditions for some regions of the country and with a development perspective. The present paper examines the role of banks in specific companies such as cement, pharmaceuticals and chemicals and offers suggestions regarding different industries and some experiences. The purpose of study was to investigate the effect of bank equity on the performance of enterprises. this study is based on econometric analysis and using the data of 26 listed companies in the period 2009 to 2013. results shows that Bank’s shareholding have a significant and positive impact on the performance of companies, as well as the type of bank shareholders, type of industry and sanctions have different and significant impact on performance.